The Effect Of Prenatal Gentle Yoga On Anxiety In 3rd Trimester Pregnant Women - Ramadhan, Fenni Valianda Amelia; Febriyani, Putri Agus (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
One form of comfort for pregnant women in the third trimester is anxiety. According to [1] around 10% of pregnant women experience mental disorders, especially depression. In developing countries, this figure is even higher, namely 15.6% during pregnancy. According to [2] the incidence of anxiety in Indonesia is 107 million pregnant women (28.7%) out of 373 million pregnant women who experience anxiety about childbirth. Pregnant women's anxiety increases in the third trimester because mothers begin to imagine the stressful birth process and the pain they will experience and even death during childbirth [3]. If anxiety is not overcome, it will affect the birth process, fetal growth and development, and can cause premature births, LBW babies, mental and motor disorders in children [4]. The aim of this research is to determine the effect of prenatal gentle yoga on anxiety in third trimester pregnant women. This research method is Quasy Experimental with a design, namely Pre and Post Test One Group Design. The total population is all pregnant women in the third trimester and sampling using purposive sampling technique obtained 35 pregnant women in the third trimester. The results of this study were changes in anxiety levels after being given prenatal gentle yoga intervention. Using the Wilcoxon statistical test, the p-value = 0.000 was obtained because it was 0.05, so H0 was rejected and Ha was accepted. The conclusion is that there is an influence of prenatal gentle yoga on the anxiety level of pregnant women in the third trimester